Early‐life density‐dependence effects on growth and survival in subantarctic fur seals. Issue 2 (21st March 2017) - Pacoureau, Nathan; Authier, Matthieu; Delord, Karine; Guinet, Christophe; Barbraud, Christophe
Abstract: Understanding the regulation of natural populations has been a long‐standing research program in ecology. Current knowledge on marine mammals and seabirds is biased toward the adult component of populations and lacking are studies investigating the juvenile component. Our goal was to estimate demographic parameters on the pre‐weaning stage of a subantarctic fur seal ( Arctocephalus tropicalis ) population on Amsterdam Island, suspected to be regulated by density‐dependence. The influence of abundance on growth parameters (length and weight) and survival was assessed over a study period spanning 16 years. We evidenced a negative trend in population growth rate when density increased. Density‐dependence models were favored for pup body size and mass growth. Abundance had a clear influence on body length at high population‐density, pups grew slower and were smaller at weaning than pups born in years with low population density. Abundance partly explained pup body mass variation and a weak effect was detected on pre‐weaning survival. The causal mechanisms may be increased competition for food resources between breeding females, leading to a reduction of maternal input to their pups. Our results suggested that pup favored survival over growth and the development of their diving abilities in order to withstand the extreme fasting periods that are characteristic of this fur seal population. This analysis provides significant insight of density‐dependent processes on early‐life demographic parameters of a long lived and top‐predator species, and more specifically on the pre‐weaning stage with important consequences for our understanding of individual long‐term fitness and population dynamics.